Resource Allocation within Firms and Financial Market Dislocation: Evidence from Diversified Conglomerates - Matvos, Gregor; Seru, Amit (Review of Financial Studies, 2014)
We argue and demonstrate that resource allocation within firms' internal capital markets provides an important force countervailing financial market dislocation. We estimate a structural model of internal capital markets to separately identify and quantify the forces driving the reallocation decision and illustrate how these forces interact with external capital market stress. The weaker (stronger) division obtains too much (little) capital, as though it is 12% (9%) more (less) productive than it really is. Out-of-sample simulated data are consistent with the actual data showing that internal capital markets offset financial market stress during the recent financial crisis by 16%–30%.